2022
DOI: 10.1007/s44155-022-00022-0
|View full text |Cite
|
Sign up to set email alerts
|

Global COVID-19 case fatality rates influenced by inequalities in human development and vaccination rates

Abstract: Aim COVID-19 has exerted distress on virtually every aspect of human life with disproportionate mortality burdens on older individuals and those with underlying medical conditions. Variations in COVID-19 incidence and case fatality rates (CFRs) across countries have incited a growing research interest regarding the effect of social factors on COVID-19 case-loads and fatality rates. We investigated the effect of population median age, inequalities in human development, healthcare capacity, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The decrease in the number of COVID-19 cases and deaths can be attributed to vaccination, income and education, as Cengiz et al [ 47 ] revealed; specifically, they inventoried the situation of COVID-19 vaccination in the cities of Turkey and established that, both in the case of women and men who have a secondary education or who have interrupted their studies at a certain moment, there is a reluctance to vaccinate, while among those who followed university studies, there is a positive correlation with this, the per capita income leading to the registration of the same trend [ 47 ]. As a whole, analyzing case fatality rates for COVID-19, Nuhu et al [ 48 ] reported the highest average in South America and the lowest in Oceania; the Africa sub-region has the smallest scores in terms of vaccination, Human Development Index (HDI) and preparedness for countering the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The decrease in the number of COVID-19 cases and deaths can be attributed to vaccination, income and education, as Cengiz et al [ 47 ] revealed; specifically, they inventoried the situation of COVID-19 vaccination in the cities of Turkey and established that, both in the case of women and men who have a secondary education or who have interrupted their studies at a certain moment, there is a reluctance to vaccinate, while among those who followed university studies, there is a positive correlation with this, the per capita income leading to the registration of the same trend [ 47 ]. As a whole, analyzing case fatality rates for COVID-19, Nuhu et al [ 48 ] reported the highest average in South America and the lowest in Oceania; the Africa sub-region has the smallest scores in terms of vaccination, Human Development Index (HDI) and preparedness for countering the pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%